PERAN PEMASARAN MEDIA SOSIAL DALAM MENCIPTAKAN KEPUTUSAN PEMBELIAN MELALUI KESADARAN MEREK (Studi pada Instagram Clothing Line Bangjo) - Yayah Robiatul Adhawiyah; Mochammad Isa Anshori (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2019)
The development and great effects of the internet are beginning to be understood by many people, and competitors have made many innovations and sales through the internet. Therefore social media marketing which is part of internet marketing was chosen as the focus of research. This study aims to determine how the influence of social media marketing on purchasing decisions through brand awareness. The independent variable studied was social media marketing (X), purchasing decision (Y) as the dependent variable, while the intervening variable was brand awareness (Z). The research approach used in this study is quantitative with explanatory methods (explanatory research). The object of research is Bangjo, a clothing business that carries out marketing through online media, Instagram. The population in this study is not known for its exact number, so that in the sample calculation a formula with an infinite population is used. The sampling technique used is non-probability sampling with purposive sampling technique. With the selected sample criteria are those who use Instagram and have made purchases on Bangjo Clothing line. Data collection techniques are carried out through observation, questionnaires, interviews and documentation. The results of the analysis show the influence of social media marketing which is able to influence the creation of brand awareness by 77.3%, social media marketing towards purchasing decisions 45.7%, brand awareness of purchasing decisions by 41%, social media marketing has impact on purchasing decisions through brand awareness by 31.7%.